2019
DOI: 10.23921/amp.2019v3i1.19251
|View full text |Cite
|
Sign up to set email alerts
|

Functional features of neutrophils in subclinical hypothyroidism compared to euthyroid status

Abstract: Neutrophils or polymorphonuclear leukocytes are critical to host defense against pathogens. Increasing evidence indicates that thyroid hormones also play an active role in immune mechanism while there is very little literature regarding effects of thyroid stimulating hormone on functional features of neutrophils. In this cross-sectional study, we evaluated the phagocytic, chemotactic, candidacidal, and respiratory burst activity of neutrophils in subclinical hypothyroid and euthyroid subjects. Phagocytosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…According to one study, there is no obvious reduction of phagocytic activity of neutrophils in hypothyroid individuals when compared to euthyroid controls. 27 This conflicting activity could be because of different methods and different cell populations studied. Our data demonstrated that the NLR index is decreased in patients diagnosed with SSS compared to the healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…According to one study, there is no obvious reduction of phagocytic activity of neutrophils in hypothyroid individuals when compared to euthyroid controls. 27 This conflicting activity could be because of different methods and different cell populations studied. Our data demonstrated that the NLR index is decreased in patients diagnosed with SSS compared to the healthy subjects.…”
Section: Discussionmentioning
confidence: 99%